Trade and Human Rights: Exploring the Impact of WTO Law on States' Capacity to Ensure the Human Right to Health - Dawar, Sandrine (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: Since the institutionalization of the General Agreement on Tariffs and Trade in 1994, the World Trade Organization has become the drive for freer trade. However, critics of the organization have complained that free trade had become inconsistent with fair trade, and that the WTO had in fact prevented states from fulfilling their human rights obligations. One particular area of concern is health. In this paper, I will analyze the nexus between WTO law and the human right to health, in an effort to identify provisions that can, in fact, assist WTO members in fulfilling their human rights obligations vis-à-vis the right to health. In applying those provisions, however, WTO members and the dispute settlement body have showed an inconsistent stance in health-related disputes, which coincides with the involvement and influence of political lobbies. It is therefore essential, to guarantee a systematic application of WTO law, in a manner consistent with WTO members' human rights obligation in health, to institutionalize an interpretive approach to WTO law in light of the right to health. Such effort can be achieved only after the relevant international human rights bodies and the NGO community stop attacking the WTO, an attitude that has proved, thus far, counterproductive, but rather collaborate with it. This approach will not only ensure the respect for the human right to health in WTO law, but will also ensure that member states will reap the economic benefits of globalization the WTO has to offer.